Successful management of total placenta previa with placenta accreta presenting with massive obstetric hemorrhage: A case report - Chanu, Sairem Mangolnganbi; Dey, Biswajit; Dey, Samarjit; Hadi, Khairul; Sharma, Nalini; Raphael, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Placenta previa and placenta accreta are important causes of serious fetal and maternal morbidity and even mortality necessitating hysterectomy. We report a case of total placenta previa with accreta in a 39-year-old female in the 32+2 weeks of pregnancy with successful delivery by cesarean. However, hysterectomy was performed to control postpartum hemorrhage.